ENHANCING THE REVENUE SYSTEM OF THE STATE BUDGET: STRATEGIC REFORMS AND THEIR SOCIO-ECONOMIC IMPACT (International Educators Conference, 2025)
Ongoing economic reforms in Uzbekistan have stimulated sustainable and balanced development by supporting private entrepreneurship, improving living standards, and ensuring macroeconomic stability. A crucial component of this progress is the modernization of the revenue system of the state budget. This article examines the effects of budget revenue structures on socio-economic development, emphasizing the need for regional financial independence, effective tax administration, and the integration of international best practices. It also explores the role of tax risk assessment systems and inter-budgetary distribution in achieving greater economic efficiency and fiscal sustainability.